TINGKAT LITERASI BUKU TEKS PELAJARAN BIOLOGI KELAS X - Hasanati Hasanati; Mariani Natalina L; Darmadi Darmadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aims to describe the level of scientific literacy textbooks of biology class X. This research uses a qualitative approach with content analysis method or document. Population in this research is all textbook of biology of class X X 2013 Curriculum used in Pekanbaru City and sample is textbook of biology curriculum 2013 class X Irnaningtyas work of publisher of Erlangga selected by purposive sampling technique. The research data is obtained from the results of the scientific literacy analysis of textbooks using the assessment instrument based on four dimensions of scientific literacy, namely science as a body of knowledge, science as a way of thinking, science as a way of investigation and interaction of science and technology society. The stages of the analysis are divided into two stages: the feasibility phase of the textbook of biology lesson and the analysis of the scientific literacy level of biology textbooks. Data analysis using descriptive statistics method. The result of data analysis shows that the most dominant dimension is science as the body of knowledge with the percentage score of 52.77%, the dimension of science as a way of thinking of 20.43%, the dimensions of science as the way of investigation of 15.40% and the dimensions of science technology interaction and the community 10.94%. Overall the level of scientific literacy of textbooks of biology class X has an average of 25% with the category less good.Key words : Literacy, Scientific Literacy, Biology Textbook.